Printing of Thin Walls using DMLS - Dana, Milan; Zetkova, Ivana; Hanzl, Pavel (Manufacturing Technology Journal, 2016)
This work deals with the problematics of 3D printing. Additive manufacturing (AM) covers a lot of principles of producing products and prototypes, for example, Direct Metal Laser Sintering (DMLS). This principle is based on sintering metal powder in thin layers, layer by layer. This theme is very extensive and a very popular research area. The paper is focused on printing thin walls. The material for printing was Maraging Steel MS1. This material achieves great mechanical properties like as high strength and high hardness. The tensile strength can be up to 2000 MPa after age hardening. The printer used was an EOS M290. The effects of different part position on safety of printing are compared. Also, the effect of support structures on accuracy was investigated. The main part of the paper is focused on an experiment where thin walls are printed and subsequently evaluated. The influences and limitations were investigated. The measurements were carried out on a Blickle Multicheck PC500 microscope.
Keywords: 3D print; DMLS; MS1 - 1.2709; Wall thickness